Real-Time Attendance Management System - Sushravya, BK; B, Swathi; Meghana, Kavali; Girisha, H (International Journal of Computer Sciences and Engineering, 2020)
The process of recording/managing attendance has been carried out since many decades. Typical process involves calling out the names of each participant serially which is manually noted down using pen-paper. We propose a secure, parallel, centralised and faster process of attendance management. A mobile application needs to be installed on the stakeholder‟s smart phone. The organiser will start the process of attendance which will generate a unique code. The code is shared with the participants (students) which are required to input it on the application. The application will check for the physical presence of the participants using the GPS co-ordinates. The organiser will immediately get the report which is also stored in a central store which can be on premise or on the cloud. This application can also be configured as a SAAS (Software as a Service) offering where multiple organisations can use the same instance of the backend application as the separation is done at the class level.